2022
DOI: 10.1371/journal.pone.0274073
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surfactant on the permeability at different positions of a leaching column

Abstract: To solve the problems of poor permeability and low leaching rate in ore heap leaching, solid surface physical chemistry, seepage mechanics theory for porous media, CT scanning and SEM were used to carry out column leaching tests with a homemade segmented removable plexiglass column; the variation law for the permeability coefficients of each segment of the leaching column before and after leaching was analyzed. The experimental results showed that there was little difference in the permeability coefficient of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…AlZaabi et al showed through relevant experiments that cationic surfactant cetyltrimethylammonium bromide had significant wettability change potential, and the increase of surfactant concentration did not necessarily lead to better wettability change. Ai et al found through the column leaching test that the addition of surfactants significantly improved the permeability of the leaching column, and the mining rate increased by about 10%. In addition, “leaching reaction coefficient” and “surface activity coefficient” were introduced.…”
Section: Introductionmentioning
confidence: 99%
“…AlZaabi et al showed through relevant experiments that cationic surfactant cetyltrimethylammonium bromide had significant wettability change potential, and the increase of surfactant concentration did not necessarily lead to better wettability change. Ai et al found through the column leaching test that the addition of surfactants significantly improved the permeability of the leaching column, and the mining rate increased by about 10%. In addition, “leaching reaction coefficient” and “surface activity coefficient” were introduced.…”
Section: Introductionmentioning
confidence: 99%